Slow Impacts on Strong Targets Bring on the Heat - H. J. Melosh; B. A. Ivanov (Geophysical Research Letters)
Abstract An important new paper by Kurosawa and Genda (2017, https://doi.org/10.1002/2017GL076285) reports a previously overlooked source of heating in low velocity meteorite impacts. Plastic deformation of the pressure‐strengthened rocks behind the shock front dissipates energy, which appears as heat in addition to that generated across the shock wave itself. This heat source has surprisingly escaped explicit attention for decades: First, because it is minimized in the geometry typically chosen for laboratory experiments; and second because it is most important in rocks, and less so for the metals usually used in experiments. Nevertheless, modern numerical computer codes that include strength do compute this heating correctly. This raises the philosophical question of whether we can claim to understand some process just because our computer codes compute the results correctly.